Cross-lagged panel analysis of reciprocal effects of metacognitive knowledge and breadth of vocabulary knowledge in a foreign language context - Teng, Mark Feng (Studies in Second Language Learning and Teaching, 2025)
Metacognitive knowledge significantly influences English vocabulary knowledge. However, few longitudinal studies have explored the reciprocal growth trajectories of metacognitive knowledge and English vocabulary knowledge over time. The present study explores how young primary school learners develop their metacognitive knowledge and vocabulary knowledge from Grade 3 to Grade 6.The longitudinal sample included 361 Grade 3 (third-year primary school) students (M = 9.60 years, SD = 0.85). The participants completed tests of metacognitive knowledge and vocabulary knowledge on four occasions. The metacognitive knowledge test focused on students’ cognitive activities, whereas the vocabulary knowledge test focused on learners’ breadth of vocabulary knowledge. Cross-lagged panel analysis was employed to explore the reciprocal effects of metacognitive knowledge and the breadth of vocabulary knowledge. The results supported the role of metacognitive knowledge in developing the breadth of vocabulary knowledge, and vice versa. Implications for young learners’ longitudinal development of metacognitive knowledge and vocabulary knowledge are discussed.